The place and value of nonsteroidal anti-inflammatory drugs in the therapy of osteoarthritis - V. V. Badokin (Современная ревматология)
The reasonability of using nonsteroidal anti-inflammatory drugs (NSAIDs) in osteoarthritis (OA) is due mainly to persistent articular tissue inflammation that contributes to the progression of structural changes in the hyaline cartilage, as well as its leading clinical manifestation – pain syndrome caused by damage to different articular structures. NSAIDs are basic rapid-acting symptom-modifying drugs in the treatment of OA. Meloxicam has high anti-inflammatory and analgesic activities. The effect of meloxicam on hyaline cartilage metabolism permits one to consider it as a potential chondroprotective agent. Short- and long-term investigations have demonstrated its good tolerability, including that in patients with polymorbidity. The use of meloxicam does not increase the risk of cardiac and renal complications. The high therapeutic activity of meloxicam along with the low level of adverse reactions determines the pharmacoeconomic expediency of its use.